The Significance of Genotypic Diversity in Coral Competitive Interaction: A Transcriptomic Perspective - Andrade Rodriguez, N.; Moya, A.; Jones, R.; Miller, D. J.; Cooke, I. R. (Frontiers in Ecology and Evolution, 2021)
Competitive interactions shape coral assemblages and govern the dynamics of coral ecosystems. Although competition is an ecological concept the outcomes of competitive interactions are ultimately determined by patterns of gene expression. These patterns are subject to genotypic variation on both sides of any interaction. Such variation is typically treated as “noise”, but it is sometimes possible to identify patterns within it that reveal important hidden factors in an experiment. To incorporate genotypic variation into the investigation of coral competitive interactions, we used RNA-sequencing to study changes in gene expression in a hard coral (Porites cylindrica) resulting from non-contact competition experiment with a soft coral (Lobophytum pauciflorum). Hard coral genotype explained the largest proportion of variation between samples; however, it was also possible to detect gene expression changes in 76 transcripts resulting from interaction with the soft coral. In addition, we found a group of 20 short secreted proteins that were expressed as a coordinated unit in three interacting Porites-Lobophytum pairs. The presence of this secretion response was idiosyncratic in that it could not be predicted based on polyp behaviour, or the genotype of hard or soft coral alone. This study illustrates the significance of individual variation as a determinant of competitive behaviour, and also provides some intriguing glimpses into the molecular mechanisms employed by hard corals competing at a distance